The impact of the 7th Asian winter games on the socio-economic development of Kazakhstan - Rakhmetulina, Zh.B.; Omurzakov А.; Rakhmetulina А. (BUKETOV BUSINESS REVIEW, 2018)
There is a link between hosting the sports mega-events and the acceleration of the pace of development of cities and countries. However, in most cases, this positive effect is short- and medium-term and occurs mainly during the preparation and hosting of the Games. A mega-event can enhance the reputation and image of the country, thereby increasing trade turnover and promoting economic growthand development hotel business. This work indicates that the 7th winter Asian games in Astana-Almaty contributed to the positive impact on social and economic development of the country,but also of hotel business. It is established that modern Asian games create the preconditions and conditions for the growth of the national economy of the host country of the Games, including the development of business and financial activity of businesses and citizens, the renovation of the infrastructure and material and technical base of production and services, the creation of new jobs and, as a result, direct impact on the growth of well-being and improvement of the quality of life of the population of the country that is hosting the Asian games. The results of the research can be used in making appropriate decisions, including monitoring the effectiveness of using budget funds and attracting private investments, during preparations for the mega-event.